Mineral composition of 'Gala' and 'Fuji' apples produced in Southern Brazil - Amarante, Cassandro Vidal Talamini do (2012)
The objective of this work was to evaluate fruit mineral composition of 'Gala' and 'Fuji' apples from orchards of different growing regions of Southern Brazil. Orchards were evaluated during the period 1991–2007 in various municipalities of the states of Santa Catarina and Rio Grande do Sul, Brazil, grouped into macroregions called Fraiburgo, Vacaria, and São Joaquim. Fruit average contents (in fresh matter) of Ca, K, Mg, N, and P were respectively 47, 1,027, 52, 419, and 116 mg kg-1 for 'Gala', and 41, 1,043, 46, 373, and 116 mg kg-1, for 'Fuji'. The means of the (K+Mg)/Ca and N/Ca ratios were respectively 24 and 9.6 for 'Gala', and 28 and 9.7 for 'Fuji'. 'Gala' and 'Fuji' apples had mean contents of Ca and P above the minimum critical levels (40 and 100 mg kg-1, respectively), while the means of the (K+Mg)/Ca and N/Ca ratios were above the maximum critical levels (30 and 14), which are considered adequate for a better postharvest quality conservation (PQC). Apples from São Joaquim orchards had the highest Ca and P, and the lowest N contents and (K+Mg)/Ca and N/Ca ratios, regardless of cultivar. The percentage of samples with fruit at high risk of poor PQC was higher for 'Fuji' than for 'Gala', regarding to Ca and P contents, and to (K+Mg)/Ca and N/Ca ratios.